Pediatric Pyomyositis: A Rare but Important Complication of Varicella - Luísa Vital; Luís Vieira; Bernardo Nunes; Frederico Raposo; Vitorino Veludo; André Pinho (Case Reports in Orthopedics)
Varicella is a common viral infection in children and most of them recover without sequelae, but serious complications can follow this infection and 6% have been reported to be musculoskeletal. A previously healthy 3-year-old Caucasian male presented with odynophagia, anorexy, fever, refusal to bear weight, and vesicular exanthema. Varicella was diagnosed, but he sustained fever around 39°C and local tenderness on the proximal lateral portion of the right leg maintaining an antalgic position. Ultrasonography and plain radiography were performed, but the magnetic resonance imaging (MRI) was performed due to the clinically worsening diagnosed pyomyositis. He was subjected to surgical debridement, and we started intravenous antibiotherapy. Streptococcus pyogenes grew in the microbiologic culture. At a 6-month follow-up, the boy did not suffer from any sequelae. The regular course of varicella is benign; however, it can occasionally develop into a more serious illness. The initial presentation of pyomyositis is often subacute, and the first symptoms may be vague. The awareness of musculoskeletal complications is imperative, and the combination of varicella’s exanthema and fever followed by some limb complaint should lead to an alert attitude.